Impact of ethical factors on job satisfaction among Korean nurses. (June 2019) - Jang, Yujin; Oh, Younjae
Background: Although numerous studies on job satisfaction among nurses have been conducted, there is a lack of research considering the ethical perspectives of leadership and organizational climate in job satisfaction. Objective: The purpose of this study was to clarify the impact of the ethical climate and ethical leadership as perceived by nurses on job satisfaction in South Korea. Research design: A descriptive and correlational study was conducted with a convenience sample of 263 nurses from four general hospitals in South Korea. Ethical considerations: This study was approved by the Institute Review Board of Hallym University before data collection. Results: Job satisfaction was positively correlated with ethical climate and ethical leadership. The ethical climate in relationship with hospitals and people orientation leadership were influential factors in the level of job satisfaction among nurses. Discussion: Organizations in the nursing environment should pay attention to improving the ethical climate with acceptable ethical norms in the workplace and nurse leaders should respect, support and genuinely care about their nurses in ethical concerns.